The purpose, tasks and functions of the National Police of Ukraine staffing - K. H. Harbuziuk (Law and Safety)
Based on the analysis of scientific views and current legislation, it was found that the purpose of staffing the National Police of Ukraine is to form a staff of qualified professionals capable of performing police tasks properly within certain job functions and in accordance with the specific needs of this central executive body. It is emphasized that the goal of staffing is achieved through solving a certain range of tasks.